The Global Orientation of Organizations: An Analysis of the Effects of Global Cultural Rationalization and National Institutional Traditions - Jan Goldenstein; Philipp Poschmann; Michael Hunoldt (Journal of Management Studies, 2022)
Most institutional studies have conceptualized institutions within the borders of national contexts as relevant to the global orientation of organizations. The world society approach in institutional theory, however, highlights the existence of a global institutional realm (i.e., driven by a process of cultural rationalization) and proposes that as a consequence of both global and national institutional demands, organizations are constructed as actors with global identities – the orientation of an organization towards the world or away from it. We argue that the global identity of organizations varies with the national institutional traditions within which organizations originate, the exposure of organizations to various instantiations of cultural rationalization within national contexts, and the extent to which organizations are governed by traditional forms of authority (i.e., family, nation state). We tested our hypotheses empirically, using data from 366 corporations listed in major stock indices in 22 countries around the globe. The empirical results support our argument.
Keywords: 650; cultural rationalization; global identity; institutional theory; institutional traditions; quantitative research; world society